Development of artificial life based optimization system - Inoue, H.; Funyu, Y.; Kishino, K.; Jinguji, T.; Shiozawa, M.; Yoshikawa, S.; Nakao, T. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Describes the computer middleware called the Hyper Artificial Life (HAL) optimization system, which is based on artificial life theories and which is effective for almost all kinds of combinatorial optimization problems in our actual world. This middleware aids the efficient development of parallel processing of an application program for combinatorial optimization problems by adopting a conventional evolution procedure. The application based on this middleware has high autonomy and high robustness, and improves its performance on a parallel computer. In this case, a supply-chain management (SCM) scheduling program, which is actually used by many users, has been applied to this middleware in parallel in order to verify and evaluate HAL. In its evaluation, we found we could obtain a remarkable improvement in the performance. This model has the characteristics of reproduction, mutation and genetics, and we found a rare phenomenon, considered as emergence in the actual result. This obviously transcends the concept of many conventional algorithms and their ability for optimization. Moreover, the model has a hyper-structure, which is why we named it the Hyper Artificial Life system.